Mechanisms Driving the Dispersal of Hydrothermal Iron From the Northern Mid Atlantic Ridge. Issue 22 (17th November 2022) - Tagliabue, Alessandro; Lough, Alastair J. M.; Vic, Clément; Roussenov, Vassil; Gula, Jonathan; Lohan, Maeve C.; Resing, Joseph A.; Williams, Richard G.
Abstract: The dispersal of dissolved iron (DFe) from hydrothermal vents is poorly constrained. Combining field observations and a modeling hierarchy, we find the dispersal of DFe from the Trans‐Atlantic‐Geotraverse vent site occurs predominantly in the colloidal phase and is controlled by multiple physical processes. Enhanced mixing near the seafloor and transport through fracture zones at fine‐scales interacts with the wider ocean circulation to drive predominant westward DFe dispersal away from the Mid‐Atlantic ridge at the 100 km scale. In contrast, diapycnal mixing predominantly drives northward DFe transport within the ridge axial valley. The observed DFe dispersal is not reproduced by the coarse resolution ocean models typically used to assess ocean iron cycling due to their omission of local topography and mixing. Unless biogeochemical models account for fine‐scale physics and colloidal Fe, they will inaccurately represent DFe dispersal from axial valley ridge systems, which make up half of the global ocean ridge crest. Plain Language Summary: Hydrothermal venting along mid ocean ridges supplies large quantities of the trace metal iron to the ocean. Once it mixed with oxygenated seawater, precipitation leads to iron being lost from the dissolved phase to generate seafloor metal deposits. However, a small fraction of iron supplied escapes precipitation and remains in the dissolved phase. The processes that control the retention and ocean transport of hydrothermal dissolved iron is important as it has a disproportionate influence on the global carbon cycle. In this work, we examined the processes driving the dispersal of dissolved iron from a major site of hydrothermal venting on the northern mid Atlantic ridge. We found that the complex topography of the mid Atlantic ridge was crucial in steering the escape of dissolved iron in the colloidal size range out of the immediate mid ocean ridge system. This raises challenges for the large scale ocean models used to represent the global ocean iron cycle as they are typically not parameterized at sufficient spatial resolution. The use of multiple grids, with higher resolution nests, may offer a solution to the challenge of representing the interactions of tracer dispersal with complex topography. Key Points: Iron is dispersed from trans Atlantic geotraverse predominantly northward within the axial valley and westward off axis, dominated by the colloidal size fraction A combination of fine‐scale processes are necessary to explain the dispersal both within and outside the axial valley Coarse resolution models are impaired in their ability to constrain the broader influence of iron supplied from axial valley ridge systems